Methadone, Pierre Robin sequence and other congenital anomalies: case–control study. Issue 2 (22nd June 2019) - Cleary, Brian; Loane, Maria; Addor, Marie-Claude; Barisic, Ingeborg; de Walle, Hermien E K; Matias Dias, Carlos; Gatt, Miriam; Klungsoyr, Kari; McDonnell, Bob; Neville, Amanda; Pierini, Anna; Rissmann, Anke; et al.
Abstract : Objective: Methadone is a vital treatment for women with opioid use disorder in pregnancy. Previous reports suggested an association between methadone exposure and Pierre Robin sequence (PRS), a rare craniofacial anomaly. We assessed the association between gestational methadone exposure and PRS. Design/setting: This case-malformed control study used European Surveillance of Congenital Anomalies population-based registries in Ireland, the Netherlands, Italy, Switzerland, Croatia, Malta, Portugal, Germany, Wales, Norway and Spain, 1995–2011. Patients: Cases included PRS based on International Classification of Disease (ICD), Ninth Edition-British Paediatric Association (BPA) code 75 603 or ICD, Tenth Edition-BPA code Q8708. Malformed controls were all non-PRS anomalies, excluding genetic conditions, among live births, fetal deaths from 20 weeks' gestation and terminations of pregnancy for fetal anomalies. An exploratory analysis assessed the association between methadone exposure and other congenital anomalies (CAs) excluding PRS. Methadone exposure was ascertained from medical records and maternal interview. Results: Among 87 979 CA registrations, there were 127 methadone-exposed pregnancies and 336 PRS cases. There was an association between methadone exposure and PRS (OR adjusted for registry 12.3, 95% CI 5.7 to 26.8). In absolute terms, this association reflects a risk increase from approximately 1–12 cases per 10 000 births. A raised OR was found for cleft palate (adjusted OR 5.0, 95% CI 2.7 to 9.2). Conclusions: These findings suggest that gestational methadone exposure is associated with PRS. The association may be explained by unmeasured confounding factors. The small increased risk of PRS in itself does not alter the risk–benefit balance for gestational methadone use. The association with cleft palate, a more common CA, should be assessed with independent data.